PENERAPAN PRINSIP KEHATI-HATIAN KOPERASI (STUDI DI KSPPS BMT MASLAHAH) - Saifuddin Syuhri; Nurul Fadila (Faculty of Islamic Economics and Business, 2020)
Prudential Principles Can Provide Protection for Cooperatives in Relation to Savings and Loans Agreements Implemented As for the precautionary principle arrangements can provide protections for cooperatives in connection with savings and loan agreements which carry out lending is one form of money lending, in a loan agreement money is often required there are debt guarantees which can consist of various forms and types. Debt guarantees in positive law in Indonesia, there are various laws and regulations that govern or relate to debt guarantees which are often referred to as collateral law. The provisions of the applicable guarantee law provide arrangements that will protect the parties concerned with the loan of money, financing and debt guarantees. The cooperative as a business entity that provides financing to Members is required to make security measures so that the financing can be paid off by the Member concerned. Financing which is not paid by the Members either in whole or in part will be a loss for the Cooperative. Losses indicate a relatively large amount that will affect the health of the Cooperative and the continuation of the Cooperative business. Therefore, no matter how small the value of money from financing that has been given to Members must remain secured in accordance with the precautionary principle. In general, financing safeguards can be carried out through the financing analysis stage and the application of applicable legal provisions. The link between credit collateral and credit security can be concluded from the provisions of Article 1131 of the Civil Code so that it is another effort or alternative that can be used by the Cooperative to obtain credit repayment when the debtor defaults. Keywords: Prudential Principle, Financing at KSPPS BMT MASLAHAH